PENINGKATAN KUALITAS PRODUK USAHA MIKRO, KECIL, MENENGAH MELALUI SERTIFIKASI HALAL DAN NIB DESA SENDURO - Mujayaroh, Anisa Lekha; Syauqiyah, Ayuning Tyas Syifaus; Khofifah, Imroatul; Junjunan, Mochammad Ilyas; Asegaf, M. Maulana; Jannah, Binti Shofiatul (Universitas Muhammadiyah Gresik, 2024)
This service activity explains assistance with halal certification and the creation of Business Identification Numbers (NIB) for Micro, Small and Medium Enterprises in increasing the marketing of local superior products in Senduro Village, Senduro District, Lumajang Regency. Seeing that there are many MSMEs in Senduro village that are not yet halal certified, the Uinsa KKN student team assisted in making Halal Certification through the SiHalal system and making NIB through the Online Single Submission System. This mentoring activity aims to assist MSME actors in improving business products through halal certification and making NIB. This assistance was welcomed by MSME actors because this assistance was able to increase product promotion and increase consumer confidence in the products produced. This assistance uses the Asset Based Community Development (ABCD) method. This method focuses on the assets and strengths that society has. The result of this halal MSME assistance activity is that it is able to increase the awareness of business actors in implementing a halal guarantee system for their business products as well as registering business units in the halal certification process through the Food, Drug and Cosmetic Study Institute of the Indonesian Ulema Council (LPPOM MUI). With the assistance of Halal Certification and the making of NIB, the community can find out about business legality. This mentoring activity really educates business people to get halal and tayyib products. The level of satisfaction of MSME actors with this assistance reached 97%.